APLIKASI ATRIBUT SEISMIK KOHERENSI CROSSCORRELATION, SEMBLANCE, DAN EIGENSTRUCTURE UNTUK DETEKSI STRUKTUR GEOLOGI PADA DATA SEISMIK 3D DI CEKUNGAN BASS, AUSTRALIA - , EDY WIJANARKO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
It has been done a study to detect fault on 3D seismic data in Bass Basin, Australia based on seismic attributes of crosscorrelation, semblance, and eigenstructure coherency. These attributes measure similarity of adjacent traces. There is a low coherency values on 3D seismic data on the detected fault. The geologic structure such as fault (dip-slip fault) system can be detected by calculating the seismic attributes coherency. The results of the analysis show that the seismic attributes of crosscorrelation, semblance, and eigenstructure coherency can be applied to detect continuity of fault on 3D seismic data in Bass Basin well which it can distinguish between the values of high coherence approximately 0.8 to 1 and low coherence values around 0 to 0.5. The use of attributes can help identify the continuity of fault. The increase of the continuity of fault on vertically seismic section and time slice seismic section is recognized plainly, so the fault can be indentified clearly too. Based on this research, the crosscorrelation-based coherence has the fastest calculation which it is about two times faster, semblance-based coherence using analytical signal has the best result as demonstrated by low coherence values are around 0 to 0.5 associated with geometric shapes of fault which it most clearly visible than the other attributes of coherence, and faultâs orientation in the study location is northwestsoutheast.